Evidence for expression and functionality of FSH and LH/hCG receptors in human endometrium - Sacchi, Sandro (J Assist Reprod Genet, 2018)
PURPOSE: Follicle-stimulating hormone (FSH) and luteinizing hormone (LH) mediate intracellular functions by binding their specific protein G-coupled gonadotrophin receptor, respectively FSH receptor (FSHR) and LH/choriogonadotrophin receptor (LHCGR). Whereas the expression of FSHR and LHCGR in mammals was considered gonad-specific and cell-specific, studies identified gonadotrophin receptors in human female extragonadal reproductive tissues. This study aims to demonstrate that gonadotrophin receptors are expressed in endometrium and mediates intracellular functions. METHODS: Collected endometria (n = 12) from healthy patients (mean age of 36 ± 6) were primary cultured for 24 h. The presence of gonadotrophin receptors was evaluated by RT-PCR followed by the sequencing of the resulted amplicons and by immunohistochemistry in original samples. Endometrial primary cultures were treated with increasing concentration (range 0–100 ng/ml) of either recombinant human LH (rhLH) or recombinant human FSH (rhFSH). Endometria controls had gonadotrophin replaced by the same volume of the culture medium. In gonadotrophin-treated samples, it was evaluated the intracellular cyclic adenosine monophosphate (cAMP) content by enzymatic immunoassay and the expression of steroidogenic genes by reverse transcriptase-quantitative polymerase chain reaction (RT-qPCR). RESULTS: The sequencing of the RT-PCR amplicons confirmed the presence of both gonadotrophin receptors and immunohistochemistry localized them on the membrane of endometrial glands cells throughout the glandular epithelium. The gonadotrophin-receptor complex was able to increase the intracellular cAMP in a dose-response and time-course manner and to induce steroidogenic genes expression. CONCLUSION: This study demonstrates that both gonadotrophin receptors are expressed along the glandular epithelium of endometria and they mediate the effects of gonadotrophins on intracellular functions. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10815-018-1248-8) contains supplementary material, which is available to authorized users.